passagem de Drummond pelo fantástico - Dias, Maria Heloisa Martins [UNESP] (My University, 2012)
It is quite possible that the story “O Gerente” (1945), by Carlos Drummond de Andrade, is unknown to the Brazilian reader, who’s more familiar with his poetry. However, the peculiarity of its narrative language and the treatment given to fantastic awakening interest in the text, which challenges the possibilities of literary research. The humor, a trait more common in the poetry of Drummond, becomes a stylistic strategy with curious effects of meaning, as well as the structural aspects of the narrative. The fantastic, a category that Drummond has not cultivated, appears so unusual in his narrative. Our purpose is to analyze the discursive construction procedures for establishing differences between the traditional and the new paradigms of the fantastic. For this, we will seek to highlight the story fragments that allow the discussion of certain issues such as social conventions, the everyday, the feeling of love, the tension created between the comic and tragic.

É bem possível que o conto “O Gerente” (1945), do escritor Carlos Drummond de Andrade, seja desconhecido do leitor brasileiro, mais familiarizado com sua poesia. Entretanto, a peculiaridade de sua linguagem narrativa e o tratamento dado ao fantástico despertam interesse pelo texto, o qual desafia as possibilidades de investigação literária. O humor, um dos traços mais presentes na poética de Drummond, se converte em uma estratégia estilística com curiosos efeitos de sentido, assim como os aspectos estruturais da narrativa. Já o fantástico, categoria que Drummond não cultivou, aparece de modo inusitado em sua narrativa. Nosso propósito é analisar os procedimentos de construção discursiva que permitem estabelecer diferenças entre a tradição e os novos paradigmas do gênero fantástico. Para isso, buscaremos destacar fragmentos do conto que permitam a discussão de algumas questões, como as convenções sociais, o cotidiano, o sentimento amoroso, a tensão criada entre a comicidade e o trágico.
Keywords: Carlos Drummond de Andrade; narrativa; fantástico; humor